ANALISIS YURIDIS TERHADAP SENGKETA KEPEMILIKAN MEREK “LEXUS” ANTARA PERUSAHAAN PT. TOYOTA JIDOSHA KABUSHIKI KAISA DENGAN PT. LEXUS DAYA UTAMA (Studi Kasus Putusan No. 194.K/Pdt/Sus/2011) - RINI KOMALASARI (PREMISE LAW JURNAL, 2016)
Brand is a mark which consists of pictures, names, words, alphabets, figures, color arrangement, of the combination of these elements which have distinctive power and are used in the activities of goods and services. The requirement/recognition on the right of brand for the brand ownership, according to constitution, is by registering it to the Directorate General of HKI as it is stipulated in Law on Brand No. 15/2001. This case began from the claim which was filed by PT. Toyota Jidhosha Kabushiki Kaisha to PT. Lexus Daya Utama. The plaintiff regarded that there was bad faith in registering a brand claimed by defendant I, PT. Lexus Daya Utama; although the registration was in different goods, there was the element of famous brand sponging from PT. Toyota Jidhosha Kabushiki Kaisha. Brand registration which has similarity in mainly and wholly different types of goods is permitted provided that it does not violate Article 4 of Law No. 15/2001and is reexamined its fame according to the provisions which discusses famous brands. Keywords: Brand Dispute, Famous Brand